Respuesta :
4+5e^(x-2)=11
4+5e^(x-2)-4=11-4
5e^(x-2)=7
5e^(x-2) / 5 = 7/5
e^(x-2)=7/5
ln e^(x-2) = ln (7/5)
(x-2) ln e = ln (7/5)
(x-2) (1) = ln (7/5)
x-2=ln (7/5)
x-2+2=ln (7/5)+2
x = ln (7/5) + 2
Answer: Otion B. x= ln (7/5) +2
4+5e^(x-2)-4=11-4
5e^(x-2)=7
5e^(x-2) / 5 = 7/5
e^(x-2)=7/5
ln e^(x-2) = ln (7/5)
(x-2) ln e = ln (7/5)
(x-2) (1) = ln (7/5)
x-2=ln (7/5)
x-2+2=ln (7/5)+2
x = ln (7/5) + 2
Answer: Otion B. x= ln (7/5) +2
Answer:
Option B is correct
Step-by-step explanation:
Given the equation: [tex]4+5e^{x-2} = 11[/tex] ......[1]
Subtraction property of equality states that you subtract the same number to both sides of an equation.
Subtract 4 to both sides in equation [1];
[tex]4+5e^{x-2} -4 = 11-4[/tex]
Simplify:
[tex]5e^{x-2}= 11[/tex]
Divide both sides by 5 we get;
[tex]\frac{5e^{x-2}}{5} = \frac{11}{5}[/tex]
Simplify:
[tex]e^{x-2} = \frac{11}{5}[/tex]
Taking log both sides we get;
[tex]lne^{x-2} = ln\frac{11}{5}[/tex]
[tex]x-2 = \ln\frac{11}{5}[/tex] Using :[tex]\ln e^x=x[/tex]
Add 2 to both sides of an equation:
[tex]x=\ln\frac{11}{5}+2[/tex]
Therefore, the solution to [tex]4+5e^{x-2} = 11[/tex] is, [tex]x=\ln\frac{11}{5}+2[/tex]